Lesley Sharp. Strange Harvest: Organ Transplants, Denatured Bodies and the Transformed Self - Marja-Liisa Honkasalo (Suomen Antropologi, 2009)
LESLEY SHARP. Strange Harvest: Organ Transplants, Denatured Bodies and the Transformed Self. Berkeley: University of California Press, 2006. Pp. 322. ISBN: 978-0-520-24784-0 (cloth); ISBN: 978-0-520-24786-4 (paper).